Achados timpanométricos em um grupo de escolares - Lindau, Tâmara De Andrade [UNESP]; Delecrode, Camila Ribas [UNESP]; Cardoso, Ana Cláudia Vieira [UNESP] (CEFAC Saúde e Educação, 2013)
PURPOSE: to characterize and compare the tympanometric findings in a group of preschoolers. METHOD: 112 preschoolers were evaluated, both genders, aged from four years old to five years and eleven months old who attended a Municipal School of Early Childhood Education in the suburbs of Marilia city- SP. Tympanometry was used as triage procedure. It was considered that the child PASSED in the triage when it presented an A type tympanometric curve, bilaterally, being reevaluated in case of failure. RESULTS: it was observed a high failure index (63.4%) in the studied population. The older female preschoolers presented a higher index of A type tympanograms, in both ears. There was a higher incidence of failure in male preschoolers aged from four years to four years and eleven months. CONCLUSION: in this sample, there was a high index of tympanometric alteration. There was a tendency among younger male students to present a higher index of tympanometric alteration when compared to older female preschoolers, this difference was not statistically significant.

OBJETIVO: caracterizar e comparar os achados timpanométricos de um grupo de escolares. MÉTODO: foram avaliados 112 escolares, de ambos os gêneros, na faixa etária de quatro anos a cinco anos e onze meses que frequentavam uma Escola Municipal de Educação Infantil, localizada em um bairro periférico da cidade de Marília. Como procedimento de triagem, utilizou-se a timpanometria. Considerou-se que a criança PASSOU na triagem quando apresentou curva timpanométrica do tipo A, bilateralmente, sendo reavaliada em caso de falha. RESULTADOS: observou-se um alto índice de falha (63,4%) na população estudada. Os escolares de maior faixa etária e do gênero feminino apresentaram um índice maior de timpanogramas do tipo A, em ambas as orelhas. Houve uma maior incidência de falha nas crianças de faixa etária entre 4 anos e 4 anos e 11 meses, e do gênero masculino. CONCLUSÃO: nesta amostra obteve-se um alto índice de alterações timpanométricas. Houve uma tendência de escolares do gênero masculino e de menor faixa etária apresentarem um índice maior de alterações timpanométricas quando comparados ao gênero feminino e de maior faixa etária, não sendo esta diferença estatisticamente significante.
Tympanometric findings in a group of students
Keywords: Audição; Pré-escolar; Triagem; Orelha Média; Testes de Impedância Acústica; Hearing; Preschool; Triage; Middle Ear; Acoustic Impedance Tests